2018
DOI: 10.1071/an16823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrated sodium calcium aluminosilicate on growth performance, fatty liver, intestine morphology, and serum parameters of overfed geese

Abstract: In geese, overfeeding induces hepatic steatosis and makes the liver functions enhanced. Aluminosilicate absorbs toxins created by moulds in animal feeds and enhances nutrient absorption. In the present study, the effects of hydrated sodium calcium aluminosilicate (Improved HSCAS, Jumpstar) on the growth performance, fatty liver, serum parameters, and intestinal morphology of overfed Landes geese were evaluated. The study included two Control groups, a non-overfed Control (Control I) and an overfed Control (Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It has been reported that the unsaturated fatty acids ( UFA ) could inhibit SFA-induced elevation of ceramides and inflammation ( Schwartz et al., 2010 ). The fatty liver of goose is more common in UFA when compared to the mammalian fatty liver, with the polyunsaturated fatty acids in particular, such as omega-3 and omega-6 ( Tang et al., 2018 ), that is, the content of SFA is 39 to 47% in the fatty liver of overfed goose ( Allard et al., 2008 ); the content of SFA is 52 to 56% in the liver of human suffered from NAFD ( Molette et al., 2001 ). It has also been reported that multiple fatty acid desaturase including stearoyl-CoA desaturase were induced in the liver of the overfed geese ( Geng et al., 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the unsaturated fatty acids ( UFA ) could inhibit SFA-induced elevation of ceramides and inflammation ( Schwartz et al., 2010 ). The fatty liver of goose is more common in UFA when compared to the mammalian fatty liver, with the polyunsaturated fatty acids in particular, such as omega-3 and omega-6 ( Tang et al., 2018 ), that is, the content of SFA is 39 to 47% in the fatty liver of overfed goose ( Allard et al., 2008 ); the content of SFA is 52 to 56% in the liver of human suffered from NAFD ( Molette et al., 2001 ). It has also been reported that multiple fatty acid desaturase including stearoyl-CoA desaturase were induced in the liver of the overfed geese ( Geng et al., 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the unsaturated fatty acids (UFA) could inhibit SFA-induced elevation of ceramides and in ammation [45]. The fatty liver of goose is more common in UFA when compared to the mammalian fatty liver, with the polyunsaturated fatty acids in particular, such as omega-3 and omega-6 [46], i.e., the content of SFA is 39-47% in the fatty liver of overfed goose [47]; the content of SFA is 52-56% in the liver of human suffered from NAFD [48]. It has also been reported that multiple fatty acid desaturase including stearoyl-CoA desaturase were induced in the liver of the overfed geese [49].…”
Section: Discussionmentioning
confidence: 99%
“…The inosine monophosphate content in the breast and thigh samples was determined using the HPLC method described by Zhang et al [ 21 ]. Total cholesterol was measured using specific assay kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China) [ 22 ]. …”
Section: Methodsmentioning
confidence: 99%